INFLUENCE OF BIODYNAMIC PREPARATIONS ON PHYSICAL PROPERTIES OF SOIL - Nykytiuk , Yu.; Tesliuk , A. (EurasianUnionScientists, 2021)
After harvesting crops, the density and hardness of the arable layer were determined from the physical properties of the soil. At the beginning of the research, the arable layer of sandy sod-medium podzolic soil was characterized by a high density, more than 1.40 g / cm3. When growing crops, the top 10 cm layer is most compacted under corn, up to 1.57–1.73 g / cm3, slightly less under cereals, up to 1.49–1.51 g / cm3.